Government regulatory policies for digital transformation in small and medium-sized manufacturing enterprises: an evolutionary game analysis - Zhu, Jianhua (2024)
In recent years, digital transformation (DT) has become an inevitable choice for manufacturing enterprises to achieve sustainable development. As a large number of enterprise groups, small and medium-sized manufacturing enterprises (SMMEs) play an important role in the industrial development of China. However, due to insufficient resource investment, high transformation costs, lack of talents, and unclear transformation pathways, how the government can help SMMEs carry out DT has become an important research topic. Based on this background, this study considers the strategies of government, third-party demonstration enterprises (TDEs) and SMMEs, develops and builds a three-party evolutionary game model, and puts forward a governance mechanism for effective DT strategies (TDEs guide DT and SMMEs conduct DT). This study has drawn many interesting conclusions. (1) If the government chooses not to regulate, when SMMEs are risk-neutral, the government only needs to increase the rewards for SMMEs to effectively promote DT. When SMMEs are risk-averse, the government needs to increase the penalties for SMMEs and increase the rewards for TDEs to effectively promote DT. (2) If the government chooses to regulate, when SMMEs are risk-neutral, the government needs to increase the penalties for both TDEs and SMMEs to effectively promote DT. When SMMEs are risk-averse, the government only needs to increase penalties on SMMEs or TDEs to effectively promote DT. (3) When SMMEs are risk-averse, the government’s best choice is regulation. Because when the government does not regulate, DT may fail even if the government increases the penalties for SMMEs and increases the incentives for TDEs.